2012
DOI: 10.1038/ncomms1859
|View full text |Cite
|
Sign up to set email alerts
|

Metformin elicits anticancer effects through the sequential modulation of DICER and c-MYC

Abstract: Diabetic patients treated with metformin have a reduced incidence of cancer and cancerrelated mortality. Here we show that metformin affects engraftment and growth of breast cancer tumours in mice. This correlates with the induction of metabolic changes compatible with clear anticancer effects. We demonstrate that microRnA modulation underlies the anticancer metabolic actions of metformin. In fact, metformin induces DICER expression and its effects are severely impaired in DICER knocked down cells. Conversely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 44 publications
14
156
0
5
Order By: Relevance
“…Given that metformin elevates DICER1 in cultured cancer cells (Blandino et al ., 2012), we wanted to examine whether changes in DICER1 expression occur in mice chronically treated with metformin and to compare these findings with those of mice on dietary caloric restriction, an intervention that extends lifespan in mice. In response to metformin and dietary caloric restriction, there is an upregulation in Dicer1 mRNA levels in the livers of treated mice compared with control mice on standard diet (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that metformin elevates DICER1 in cultured cancer cells (Blandino et al ., 2012), we wanted to examine whether changes in DICER1 expression occur in mice chronically treated with metformin and to compare these findings with those of mice on dietary caloric restriction, an intervention that extends lifespan in mice. In response to metformin and dietary caloric restriction, there is an upregulation in Dicer1 mRNA levels in the livers of treated mice compared with control mice on standard diet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As DICER1 also plays other important roles in the RNA‐induced silencing complex (RISC) and in RNA metabolism (Burger & Gullerova, 2015), we cannot exclude the possibility that these other functions of DICER1 may be altered by metformin and contribute to metformin signaling. In addition, upregulation of DICER1 by metformin may also be regulated, in part, at the transcriptional level (Blandino et al ., 2012); a comprehensive view of the spectrum of DICER1 functions influenced by metformin is beyond the scope of this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Then, it was demonstrated that stromal cells may perform aerobic glycolysis under the influence of tumor cells and donate lactate to feed OxPhos metabolism of tumor cells, the so-called "Reverse Warburg Effect." [39][40][41] Metformin, a drug that is found to be effective in tumors, [42][43][44][45] when it was added in acidic medium, which will be used for MSC conditioning, blocks TGFb expression and reverts inhibition of GLUT 1 and 3 elicited by acidic medium in MSC. Moreover, melanoma cells conditioned by LpH-metformin-treated MSC medium exhibited a reconstituted epithelial-like profile and a reduced invasion, that were associated with a reduction of GLUT 1, 3.…”
Section: Discussionmentioning
confidence: 99%
“…As a result antidiabetic drugs such as metformin, which is currently taken by 100 million people worldwide, are being explored for anti-tumor activity [144][145][146]. Multiple epidemiological studies show that diabetic patients treated with metformin have reduced incidence of cancer and reduced cancer mortality [145].…”
Section: Metformin: From Diabetes To Cancer Therapymentioning
confidence: 99%